En toe laat die maan haar stem hoor: Genesis 1 en feministiese teologie - Claassens, LJM (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
And the Moon Spoke Up: Genesis 1 and Feminist Theology In this essay, Genesis 1 is read in terms of the twofold task of a feminist biblical interpreter, i.e. to deconstruct harmful interpretations that uphold hierarchies with regard to race, class and gender, and to reconstruct interpretations that offer a vision of God’s relationship to the world that is committed to end oppression and injustice in a society deeply wounded. Employing insights from deconstruction and feminism, this paper utilises an intriguing rabbinic interpretation from the Talmud with regard to one of the binary oppositions in Genesis 1, i.e., the great light and the small light, or one could say, the sun and moon (Hullin 60). This midrash is used to challenge the hierarchical interpretations of the binary oppositions in this text, thereby opening up the space for alternative interpretations to emerge. Consequently, this interpretative strategy also helps us to also rethink the hierarchical nature of the other binary oppositions in Genesis 1 and its interpretations.